Manuel-Reyes García Hurtado (Ed.). The United Kingdom and Spain in the Eighteenth Century. Beloved Enemy. Routledge, 2025, 382 pp. - Sisto Reija, Sebastián Daniel (2026)
Revisión del libro The United Kingdom and Spain in the Eighteenth Century. Beloved Enemy por M. Reyes García Hurtado